2020
DOI: 10.1109/tlt.2020.2989776
|View full text |Cite
|
Sign up to set email alerts
|

Toward Personalized Scaffolding and Fading of Motivational Support in L2 Learner–Dialogue Agent Interactions: An Exploratory Study

Abstract: This study proposes a computer-based approach to effectively enhance second language learners' willingness to communicate in the target language. To do so, we implemented a conversational agent embedding a dialogue management model based on two conversational strategies (i.e., communication strategies and affective backchannels), serving as scaffolds for enhancing learners' willingness to communicate in the target language. Here, we report on differences observed among second language learners' preferences for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Ayedoun et al. (2020) find that Communication Strategies (CS) and Affective Backchannel (AB) have a positive impact on student perceptions. The authors observed that learners with a lower willingness to communicate tend to prefer AB over CS, while their counterparts with higher willingness to communicate tend to favour CS over AB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayedoun et al. (2020) find that Communication Strategies (CS) and Affective Backchannel (AB) have a positive impact on student perceptions. The authors observed that learners with a lower willingness to communicate tend to prefer AB over CS, while their counterparts with higher willingness to communicate tend to favour CS over AB.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, affective feedback involves fostering a creative environment, giving students confidence and motivating students to think that the lesson goals are achievable and to become more involved in the learning activities. Ayedoun et al (2020) find that Communication Strategies (CS) and Affective Backchannel (AB) have a positive impact on student perceptions. The authors observed that learners with a lower willingness to communicate tend to prefer AB over CS, while their counterparts with higher willingness to communicate tend to favour CS over AB.…”
Section: Student Perceptionsmentioning
confidence: 91%
“…(2015) Multimodal response generator To foster L2 learners' willingness to communicate in L2 N/A The approach decreases students' nervousness while increasing their self-confidence Ayedoun et al. (2019) Conversation agent, Jack To foster learners' readiness toward communication in a second language 40 Japanese university students Enhancing L2 learners' participation in contact and communication Ayedoun et al. (2020) An embodied conversational agent, Peter To encourage students to converse in the target language.…”
Section: Resultsmentioning
confidence: 99%
“… Approaches Authors and Year Name of the Chatbot Empathy Dimensions Affective Approaches Wu et al. (2022) An innovative affective mobile language tutoring system (AMLTS) The stress relief module The emotion recognition module Ayedoun et al. (2020) An embodied conversational agent, Peter Backchannels emotion-sensitive support Xie et al.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these, metacognitive scaffolding is the most appropriate to promote higher order thinking, helping students reflect on what they have learned, and assisting individual learning management (Reingold et al, 2008 ; Teo & Chai, 2009 ). One instance of this, although not a chatbot, would be Ayedoun et al’s ( 2020 ) computer-based approach to teach students with different levels of willingness using varied scaffolding and fading strategies. In moving towards a more adaptive educational chatbot, our system can benefit by incorporating more scaffolding theory and working examples.…”
Section: Discussionmentioning
confidence: 99%